The Feature of Female Imagesin Uzbek and German Folk Tales - Mansurova Karomat Khabibullaevna (Research Parks Publishing LLC, 2022)
This article discusses about the main women’s appearances in the tales of the Uzbek and German nations. Their most common incarnations and characteristic features are revealed for more details.